2018
DOI: 10.1155/2018/8626102
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Investigation of Risk Factors Affecting Lumbar Spine Injuries Using a Detailed Lumbar Model

Abstract: Recent field data showed that lumbar spine fractures occurred more frequently in late model vehicles than early ones in frontal crashes. However, the lumbar spine designs of the current crash test dummies are not accurate in human anatomy and have not been validated against any human/cadaver impact responses. In addition, the lumbar spines of finite element (FE) human models, including GHBMC and THUMS, have never been validated previously against cadaver tests. Therefore, this study developed a detailed FE lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The innovation of this approach was to predict the specific numerical value of the natural frequency of the human lumbar spine by using the porous seepage-stress coupled FE analysis [32]. Initially, a real time-dependent vibrational condition was simulated, and the changes in lumbar mechanical parameters with time were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The innovation of this approach was to predict the specific numerical value of the natural frequency of the human lumbar spine by using the porous seepage-stress coupled FE analysis [32]. Initially, a real time-dependent vibrational condition was simulated, and the changes in lumbar mechanical parameters with time were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Referring the literatures [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , the prevailing causes are recognized causes that have a greater influence on lumbar spinal damage during a frontal collision. We are I drop height, (ii) sitting angle posture, and (iii) upper body mass.…”
Section: Experimental Workmentioning
confidence: 99%
“… If the magnitude of masses was lesser than 15 kg, the energy absorption is reduced to the lower level. During lower energy tests, the specimen did not sustain injuries which allowed further evaluation for sub-failure and failure tests of biomechanical data from the same specimen [37] , [38] . If the magnitude of masses was greater than 35 kg, the energy absorption is unpredictable.…”
Section: Experimental Workmentioning
confidence: 99%
“…This feature offers the possibility of estimating the risk of fractures or damage to human soft tissues. One of the road traffic injuries with the most serious long-term consequences is a lumbar spine section injury ( Zheng, Tang & Hu, 2018 ; Muller et al, 2014 ; El-Rich et al, 2009 ; Fradet et al, 2014 ; Eberlein, Holzapfel & Frohlich, 2004 ). Several new field studies have shown that lumbar spine fractures occur more frequently in new vehicle models than in previous models ( Kaufman et al, 2013 ; Muller et al, 2014 ; Pintar et al, 2014 ; Doud et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%